Effectiveness on major cardiovascular risk factors of an educational program to promote a Mediterranean type of diet among the employees of the company FCA Italia S.p.A. (September 2021) - Clemente, Gennaro; Giorgini, Marisa; Della Pia, Nila; Cerbara, Loredana; Liuzzi, Raffaele; Cipriano, Paola; Riccardi, Gabriele; Vaccaro, Olga
Abstract: Aims: The educational program implemented at the Pratola Serra (Avellino, Italy) facility of the company FCA (Fiat Chrysler Automobiles), had as its goal to raise awareness among people to adopt behaviors inspired by the principles of a Mediterranean diet, physical activity and prevention of the main cardiovascular risk factors. Methods: The educational program was implemented in two different ways in order to compare, according to an intervention-control scheme, the performance of the subgroups and the effect of the types of intervention. On both groups measurements of the vital parameters were carried out and compared by means of statistical probabilistic tests. Results: The educational intervention was shown to be effective in: encouraging healthy food choices both in the workplace and at home (with a statistically significant reduction in caloric intake, animal protein, saturated fatty acids, cholesterol and glycemic load and an increase in vegetable proteins), significantly increasing physical activity and reducing body weight, body mass index, waist circumference, total cholesterol, LDL cholesterol and blood glucose in the participants. Conclusions: The educational campaign proved effective in increasing the well-being of the participants, confirming the effectiveness of a multifactorial intervention based on the promotion of a dietary model rather than individual foods.